Effect of Brazilian propolis on experimental hepatotoxicity in rats - Fernandes, A. A H [UNESP]; Fernandes, A. [UNESP]; Novelli, E. L B [UNESP] (My University, 2004)
Propolis (bee glue) is one of the major hive products of bees and is rich in flavonoids, which are known for their antioxidant activities. The aim of this study was to evaluate the hepatoprotective effects of the ethanolic extract of propolis (EEP) against experimental carbon tetrachloride (CCl 4)-induced liver toxicity in rats by means of biochemical indices. The animals were divided into 4 groups: GI= received mineral oil; GII= CCl 4(4mL/kg; Lp., single dose) treated; GIII= CCl4 (4mL/kg; i.p., single dose) treatment followed by ethanolic extract of propolis (100mg/kg) for gavage from the species Tetragonisca angustula, daily for 3 days and GIV= CCl4 (4mL/kg; i.p., single dose) treatment followed by ethanolic extract of propolis (100mg/kg) for gavage from the species Nannotrigonea testaceicornes, daily, for 3 days. The serum levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), cholesterol and triacylglycerols were estimated after 3 days. CCl 4 caused a maximum increase (p<0,01) above biochemical parameters. As compared to CCl4 group (GII), the EEP (GIII and GIV) showed reduction in cholesterol, triacylglycerol, ALT, AST and alkaline phosphatase activity in the serum. In conclusion, these data indicate that EEP improved the dyslipidaemia, moreover, significantly attenuated increases in serum ALT and AST activities in rats with liver damage induced by carbon tetrachloride.
Keywords: Biochemistry; Carbon tetrachloride; Hepatotoxicity; Propolis; Protection; alanine aminotransferase; alcohol; alkaline phosphatase; carbon tetrachloride; cholesterol; mineral oil; propolis; triacylglycerol; alanine aminotransferase blood level; alkaline phosphatase blood level; animal experiment; animal model; controlled study; drug effect; drug isolation; dyslipidemia; enzyme activity; feeding; liver protection; liver toxicity; male; medicinal plant; nannotrigonea testaceicornes; nonhuman; rat; tetragonisca angustula; triacylglycerol blood level